Architectural design management : The development of best practices model based on the quality management system requirements - 174499 Abdul Hakim Mohamed; Universiti Teknologi Malaysia. Fakulti Kejuruteraan dan Sains Geoinformasi (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL